2005
DOI: 10.1016/j.rmed.2004.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nasal continuous positive airway pressure in uncontrolled nocturnal asthmatic patients with obstructive sleep apnea syndrome

Abstract: The mechanisms of nocturnal asthma are intimately related to circadian rhythms, which influence inflammatory cells and mediators, hormone levels and cholinergic tone. Nocturnal airway narrowing in asthma is sometimes associated with sleep disorders, such as obstructive sleep apnea syndrome (OSAS). The aims of this study were to evaluate the association of nocturnal asthma and OSAS, and investigate the influence of continuous positive airway pressure (CPAP) therapy to improve nighttime symptoms in asthmatic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 14 publications
5
102
0
3
Order By: Relevance
“…The first studies, carried out in the 1980s, consisted in series of 9‐10 patients followed sometimes for only 2 weeks 14, 15. More recently, other groups have confirmed the positive effects of treating OSAS (in adults using CPAP and in children undergoing adenoidectomy and tonsillectomy) in the clinical course of asthma 10, 17, 18, 19. In contrast, the effects of CPAP therapy on pulmonary function of asthmatic patients with OSAS are less common and limited to small improvements in blood gases 16 or small increases (around 10%) in the peak expiratory flow rate 14.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The first studies, carried out in the 1980s, consisted in series of 9‐10 patients followed sometimes for only 2 weeks 14, 15. More recently, other groups have confirmed the positive effects of treating OSAS (in adults using CPAP and in children undergoing adenoidectomy and tonsillectomy) in the clinical course of asthma 10, 17, 18, 19. In contrast, the effects of CPAP therapy on pulmonary function of asthmatic patients with OSAS are less common and limited to small improvements in blood gases 16 or small increases (around 10%) in the peak expiratory flow rate 14.…”
Section: Discussionmentioning
confidence: 92%
“…In patients with OSAS and concomitant asthma, application of continuous positive airway pressure (CPAP) has been reported to provide benefits for asthma, although, in general, these studies included a small number of subjects, lacked of a control arm, were retrospective, had relatively short follow‐up times, and used heterogeneous criteria for the assessment of outcomes, which limit the consistency of their conclusions 14, 15, 16, 17, 18. In a recent survey among 1586 patients with OSAS of which 12.4% were asthmatics, long‐term treatment with CPAP (mean of 5.7 ± 4.7 years) was effective in reducing asthma symptoms and improving asthma control in 152 patients 19.…”
mentioning
confidence: 99%
“…88 In less severe asthmatics no change was seen in FEV 1 or the provocational concentration of a bronchial agonist causing a 20% decrease in FEV 1 ; however, asthma quality of life scores improved a clinically important amount, suggesting unmeasured improvements in lung function during sleep. 89,90 Ongoing studies may help answer questions about mechanism and the role that treatment has on modifying asthma.…”
Section: Other Overlap Syndromesmentioning
confidence: 99%
“…Several authors have reported a relationship between asthma and OSA [8][9][10][11][12][13][14]. The prevalence of OSA is higher among patients with adult asthma; OSA symptoms, which further deteriorate asthma symptoms, are commonly observed in the asthmatic population; thus, treating OSA can improve asthma symptoms [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%